1978
DOI: 10.1037/0021-843x.87.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Learned helplessness and depression in a clinical population: A test of two behavioral hypotheses.

Abstract: This study was undertaken to extend the learned helplessness phenomenon to a clinical population and to test the competing hypotheses of Seligman and Lewinsohn. Ninety-six male hospitalized psychiatric and medical patients were divided into three levels of depression according to their scores on the Short Form of the Beck Depression Inventory. Subjects were randomly assigned to one of four experimental conditions: (a) One group was treated with an 80-dB tone, which could be terminated by making an active respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Previous research has shown that current depression can moderate the effects of controllable stress on cognitive task performance (Klein et al, 1976; Miller and Seligman, 1976; Price et al, 1978). In addition, sex differences in physiological and psychological responses to stress are consistently noted in stress research (e.g., Ordaz and Luna, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that current depression can moderate the effects of controllable stress on cognitive task performance (Klein et al, 1976; Miller and Seligman, 1976; Price et al, 1978). In addition, sex differences in physiological and psychological responses to stress are consistently noted in stress research (e.g., Ordaz and Luna, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have defined uncontrollability as non-contingency between instrumental actions and outcomes (Oakes and Curtis, 1982), as repeated failure feedback regardless of responses (Klein et al, 1976; Jones et al, 1977; Kilpatrick-Tabak and Roth, 1978; Hirt and Genshaft, 1981) or as both non-contingency and failure (Hiroto, 1974; Hiroto and Seligman, 1975; Benson and Kennelly, 1976; Klein and Seligman, 1976; Miller and Seligman, 1976; Price et al, 1978; Kofta and Sedek, 1989). We structured the manipulation of uncontrollability to include both non-contingency and increased rates of failure.…”
Section: Methodsmentioning
confidence: 99%
“…Metacognitive skills are thought to be necessary for effective problem solving (Flavell, 1976;Slife et al, 1985), and research has indicated that depressives are often relatively poor problem solvers (Klein, Fencil-Morse, & Seligman, 1976;Price, Tryon, & Raps, 1978). General metacognitive skill has typically been divided into two components: knowledge about cognition and regulation of cognition (Brown, 1975(Brown, , 1977Brown & Palinscar, 1982;see Cavanaugh & Perlmutter, 1982, for a similar distinction).…”
Section: Slife and Weavermentioning
confidence: 99%
“…109-120) reported impaired performance on cognitive tasks following uncontrollable electric shock, but no deficits following an equal number of controllable shocks. Rodin (1976), Benson and Kennelly (1976), and Cohen, Rothbart, and Phillips (1976) used a cognitive induction (insolvable problems) and reported interference on performance of cognitive tasks, as did , Klein, Pencil-Morse, andSeligman (1976), Teasdale (1978), and Price, Tryon and Raps (1978). reported shuttlebox learning deficits following exposure to ines capable noise which were reversed by a "therapy" consisting of solvable problems.…”
Section: Motivational and Cognitive Effectsmentioning
confidence: 99%